(untitled) (Texas Journal of Medical Science, 2024)
This article explores the often-overlooked domain of pediatric gynecology, focusing on sexual azo defects and disorders of the menstrual cycle in children and adolescents. Through an extensive literature analysis, the study investigates the prevalence, causes, and potential interventions for these conditions. The methods section details the approach taken, followed by the results, discussion, and concluding with practical suggestions for healthcare practitioners dealing with young patients in this field